UNDERSTANDING BARRIERS IN RESPIRATORY EQUIPMENT IMPLEMENTATION AMONG WILDLAND FIREFIGHTERS - Rodriguez, Aida C (East Carolina University)
Background: Over the past decade, awareness has grown among wildland firefighters about the health risks associated with smoke exposure and cancer. In June 2022 the International Agency for Research on Cancer (IARC) reclassified occupational exposure for firefighters as Group 1, carcinogenic to humans. However, limited data exist on respiratory protection practices, perceived barriers to adopting protective equipment, and chemical risk knowledge among firefighters. Understanding these gaps and barriers is essential for developing effective protection protocols and education programs. Specific Aims: This study aimed to evaluate firefighters' chemical risk knowledge of smoke produced in wildland/Wildland Urban Interface (WUI) fire incidents, identify knowledge and perception gaps between leadership and non-leadership levels, and explore attitudes, barriers and motivators to respiratory protection across leadership roles. Methods: A mixed-methods approach was employed using The Wildfire Conservancy Respiratory Protection Survey (n=766) and key informant interviews with non-leadership and leadership firefighters (n=27). In the quantitative analysis, data were analyzed using RStudio (version 2024.04.2+764) and the qualitative thematic analyses were conducted using Dedoose (version 9.2.012). The study applied Social Cognitive Theory to investigate cognitive, behavioral, and environmental factors influencing the use of respiratory protection among wildland firefighters. Results: The Wildfire Conservancy Survey revealed that 85.9% of firefighters do not use respiratory protection during wildland/WUI incidents, with cloth masks being the most commonly used form of respiratory protection (67.8). Significant knowledge gaps were found regarding hazardous chemical produced by smoke. No significant differences in chemical knowledge were observed between firefighters in leadership versus non-leadership (p-value=0.646). Impaired breathing (64.2%) emerged as a major barrier in respiratory protection. Leadership exhibited significantly more concern about the size of the respiratory equipment (p-value=0.004), whereas non-leadership firefighters placed greater importance on the appearance of the equipment (p-value=0.004). Cancer risk reduction (74.8%) was the strongest health motivator for respiratory protection use for both leadership and non-leadership. Key informant interviews highlighted leadership's influence on respiratory protection adoption, with non-leadership firefighters being less likely to adopt protection due to cultural norms and perceived feasibility. Discussion: Significant knowledge gaps regarding smoke exposure risks and respiratory protection exist among wildland firefighters. Targeted training across all ranks is needed to raise awareness, and leadership must model protective behavior to improve equipment adoption. Current respiratory methods are inadequate, underscoring the need for effective, practical solutions. Addressing cultural norms that discourage safety measures and creating a national standard for respiratory protection are essential for fostering safer wildland firefighting practices.
Keywords: Wildland Firefighters; Perceived Barriers; Respiratory Protection; Knowledge Gaps; Occupational Health; Firefighters